Prevalence of Intestinal Parasitic Helminths Infection (IPHI) in Patients Attending Microbiological Laboratory of Tishreen University Hospital in Lattakia/Syria between 2016-2019 - Dayoub, Amal Ebrahim (Latakia University Journal -Biological Sciences Series, 2020)
This study was conducted to investigate intestinal parasitic helminths (IPH), and detect their species and prevalence with inhabitants of Lattakia, through following laboratorial examination for stool samples of patients of microbiological laboratory in Tishreen University Hospital in Lattakia between 2016-2019. The results of the study showed prevalence of intestinal helminthes infection in Lattakia; 7 species of intestinal helminthes were recorded: 3 species of nematode were: Enterebius vermicularis, Ascaris lumbricoides, and Ancylotstoma dudenale( Hook worm), and 4 species of Platehelminthes, two of them belonged to Class: Trematoda were: Paragonimus westermani, and Schistosoma mansoni, and two species belonged to Class: Cestoda were: Hymenolepis nana and Taenia saginata, the infection of Ancylotstoma dudenale, Paragonimus westermani, and Schistosoma mansoni was recorded for the first time in Syria. The general prevalence of infection with intestinal helminthes of patients attending microbiological laboratory of Tishreen University Hospital in Lattakia during the period of 2016-2019 was 1.98%. The majority of them were infected with only one species of intestinal helminthes, while only two cases of double infection were recorded: the first with both species (Enterebius vermicularis and Ascaris lumbricoides), and the second with both species ( Ancylotstoma dudenale, and Paragonimus westermani). This study showed that Enterebius vermicularis was the most common intestinal helminthes in Lattakia governorate as 0.92%, followed by Ascaris lumbricoides and Ancylotstoma dudenale. In general, males were more infected than females. However, the highest infection rate was recorded in winter and autumn of 2016 and 2017 whilst it was seen in summer and autumn of 2018 and summer of 2019. أجريت الدراسة بهدف التقصي عن الإصابة بالديدان الطفيلية المعوية عند السكان في محافظة اللاذقية، وتحديد أنواعها ونسبة انتشارها من خلال متابعة الفحص المخبري لعينات البراز للمرضى المراجعين لمخبر الأحياء الدقيقة في مشفى تشرين الجامعي باللاذقية خلال الأعوام 2016-2019. بينت نتائج الدراسة انتشار الإصابة بالديدان الطفيلية المعوية عند السكان في محافظة اللاذقية، حيث تم تسجيل 7 أنواع؛ 3 أنواع من الممسودات Nematoda هي: (الحرقص او السرمية الدودية Enterebius vermicularis، والصفر الخراطيني (الأسكارس) Ascaris lumbricoides، والملقوات العفجية (الدودة الكلابية Hook worm) Ancylotstoma dudenale. و4 أنواع من الديدان المسطحة Platehelminthes : نوعان منها ينتميان لصف المثقوبات Class:Trematoda هما: جانبية المناسل الوسترمانية Paragonimus westermani والمنشقة المانسونية Schistosoma mansoni، ونوعان ينتميان لصف الشريطيات Class: Cestoda هما المحرشفة القزمة Hymenolepis nana و الشريطية العزلاء Taenia saginata . سجلت الإصابة بالملقوة العفجية، وجانبية المناسل الوسترمانية، والبلهارسيا المانسونية لأول مرة في سورية في دراستنا هذه. بلغ معدل الانتشار العام للإصابة بالديدان الطفيلية المعوية عند المرضى المراجعين لمخبر الأحياء الدقيقة في محافظة اللاذقية خلال الأعوام 2016-2019 حوالي 1.98%. كانت الأغلبية العظمى منهم مصابين بنوع واحد فقط من الديدان المعوية، بينما سجلت حالتين فقط لخمج مضاعف: الأولى بالنوعين (الحرقص والاسكارس)، والثانية بديدان النوعين (الملقوة العفجية وجانبية المناسل الوسترمانية). أظهرت الدراسة أن الحرقص من أكثر الديدان المعوية انتشاراً عند السكان في محافظة اللاذقية 0.92%، يليها الاسكارس، ثم الملقوات العفجية. كما تبين أن الإصابة عند الذكور كانت أعلى منها عند الإناث، وقد سجلت أعلى قيم للإصابة في فصلي الشتاء والخريف خلال العامين 2016-2017، بينما اقتصرت على فصلي الصيف والخريف في العام 2018، وعلى فصل الصيف في العام 2019.